Modeling and solving the waste valorization production and distribution scheduling problem - Chagas, Guilherme O.; Coelho, Leandro C.; Darvish, Maryam; Renaud, Jacques (European journal of operational research, 2023)
•We model and solve the waste valorization production and distribution scheduling problem.•We introduce several formulations for this difficult and rich problem.•We design production and distribution schedules of several types of fertilizers.•We determine how critical parameters affect the performance of the system.•We show the possibility of optimizing important tactical production and delivery scheduling decisions efficiently. Bio-based waste valorization is one of the current trends in municipal waste management. It decreases the amount of waste to be disposed of, reduces the sourcing of limited chemical compounds used in fertilizer production, and promotes a circular economy perspective vital in big cities. However, modeling and optimizing a biorefinery plant’s operations is challenging and requires innovative approaches and solutions. In this paper, we model and solve the integrated production and distribution scheduling problem faced by an industrial partner. We propose three models for the waste valorization production and distribution scheduling problem: a time-discretized integer linear program, and two mixed-integer linear program with continuous timing variables. Moreover, several powerful and problem-specific valid inequalities and variable reduction procedures are proposed. We study some variants of the problem and propose a simple heuristic algorithm that mimics the logic of a decision maker. Through a series of computational experiments, we determine how critical operational parameters affect the performance of the system and demonstrate how significant improvements can be achieved in our industrial partner’s biorefinery plant.